Using Satellite AIS to Analyze Vessel Speeds Off the Coast of Washington State, U.S., as a Risk Analysis for Cetacean-Vessel Collisions - Greig, Nathan C.; Hines, Ellen M.; Cope, Samantha; Liu, XiaoHang (Frontiers in Marine Science, 2020)
Most species of whales are vulnerable to vessel collisions, and the probability of lethality increases logistically with vessel speed. Spatially explicit risk assessments can inform the marine management process about the potential for vessel collisions. We used Satellite Automatic Identification Systems (SAIS) data from 2013 and 2014 to calculate vessel speed over ground around the Olympic Coast National Marine Sanctuary. Nearby shipping lanes connecting the Ports of Vancouver, Seattle, Tacoma, and Portland have the greatest density of vessel traffic arriving and departing, and these densely traveled routes continue outside the US Exclusive Economic Zone. We characterized speed and density based on vessel type and for areas of interest, including NOAA’s Cetacean Density and Distribution Working Group’s Biologically Important Areas. Cargo and tanker vessels constitute the majority of distance traveled at the greatest speeds. We found that calculated speed based on SAIS is higher and less variable than broadcast speed for most vessel types. It is important to use calculated speed over ground (SOG) in any analysis so that the risk from potential vessel collisions is not underestimated by using broadcast SOG. Temporal gaps in the SAIS data led to a resulting systematic underestimation of vessel speed in calculated speed over ground. In that case, SAIS can be helpful in documenting minimum vessel speeds across large geographic areas, especially beyond the reach of terrestrial AIS receivers. Satellite AIS is useful in examining vessel density at broad scales, and could be used to assess basin-wide open ocean routes. Future use of additional satellite platforms with AIS receivers will only increase the quality of SAIS data and decrease the amount of temporal gaps.